2020
DOI: 10.1016/j.redox.2019.101318
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Aurora A regulation by the metabolic integrator coenzyme A

Abstract: Aurora A kinase is a master mitotic regulator whose functions are controlled by several regulatory interactions and post-translational modifications. It is frequently dysregulated in cancer, making Aurora A inhibition a very attractive antitumor target. However, recently uncovered links between Aurora A, cellular metabolism and redox regulation are not well understood. In this study, we report a novel mechanism of Aurora A regulation in the cellular response to oxidative stress through CoAlation. A combination… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
71
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 84 publications
(134 reference statements)
3
71
0
1
Order By: Relevance
“…It was found that CoA was able to form a disulfide adduct (CoAlation) on Cys-290 within the AURKA activation segment, near the conserved Thr-288 autophosphorylation/activation site. 4 A crystal structure of an AURKA kinase domain CoAlated on Cys-290 and phosphorylated at Thr-288 revealed a monomeric kinase domain with the adenosine diphosphate (ADP) moiety of CoA occupying the adenosine triphosphate (ATP) binding pocket, consistent with an inhibitory effect. CoAlation as well as oxidation of Cys-290 to sulfenic acid were found to be stimulated in mammalian cells artificially treated with oxidizing agents, suggesting a possible link between increased protein thiol oxidation during mitosis and AURKA regulation.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that CoA was able to form a disulfide adduct (CoAlation) on Cys-290 within the AURKA activation segment, near the conserved Thr-288 autophosphorylation/activation site. 4 A crystal structure of an AURKA kinase domain CoAlated on Cys-290 and phosphorylated at Thr-288 revealed a monomeric kinase domain with the adenosine diphosphate (ADP) moiety of CoA occupying the adenosine triphosphate (ATP) binding pocket, consistent with an inhibitory effect. CoAlation as well as oxidation of Cys-290 to sulfenic acid were found to be stimulated in mammalian cells artificially treated with oxidizing agents, suggesting a possible link between increased protein thiol oxidation during mitosis and AURKA regulation.…”
mentioning
confidence: 99%
“…CoAlation as well as oxidation of Cys-290 to sulfenic acid were found to be stimulated in mammalian cells artificially treated with oxidizing agents, suggesting a possible link between increased protein thiol oxidation during mitosis and AURKA regulation. [3][4][5] Treatment of cells with oxidizing agents has been shown to stimulate AURKA phosphorylation at Thr-288. 4,6 Yet, paradoxically, in biochemical assays using purified protein, oxidative modification of AURKA by CoAlation or sulfenylation of Cys-290 potently inhibited kinase activity.…”
mentioning
confidence: 99%
See 3 more Smart Citations